Pemanfaatan Limbah Sabut Kelapa pada Perencanaan Interior dan Furniture yang Berdampak pada Pemberdayaan Masyarakat Miskin - Titi Indahyani (Humaniora, 2011)
Coconut coir is one component of coconut that could be produced and decomposed into products needed by domestic or international market. Cocofiber and cocopeat are two derived products from coconut coir which through several researches could be produced into supporting material of interior and furniture, including matrass, bed sofa, and particle board like MDF, Coconut Fiber Board (CFB). Within this research, it is hoped to distribute the information about the functions and producing materials from coconut coir waste. This is supposed to be used by the government, minor industry, designer, and public to also apply and choose environment-friendly coconus coir material and sustain as a part of sustainable design, green design, social entrepreneurship and related programs. Therefore, coconut coir waste could be valued economically and has its positive effects to society who live around the coconut tree plantation area.